Marshallian External Economies and Optimal Tax-Subsidy Structure - Aoki, Masahiko (Econometrica, 1971)
[The problem of an optimal tax-subsidy scheme under which a socially optimal point is maintained through the competitive market mechanism in the presence of external economies of scale is discussed. The scheme is compared to the doctrine developed by Marshall, Pigou, Kahn, and Lerner.]